NALAR KEISLAMAN URANG BANJAR - Muhammad Iqbal Noor (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
This paper speaks about the development of Islamic Banjar people reason in historical and philosophical approach. Started with the introduction of Islamic reason and banjar people as the subject and object studies. Then will be discussed about the development of religion reason and the Islamic banjar reason historically and philosophically. The writer in his paper states that the pre-mystical Islamic religion reason has changed to the mystical Islamic reason, then grew and developed to be a formal Islamic reason and finally became the Islamic scientific reason that did not grow yet fully. Actually, the development of a reason to the other is not a linier thing or change each other but its overlapping, that when come the new reason the old one is still exist.